Homogeneity or Heterogeneity? An Insight into the Dilemma that exists in Cross-Cultural Management Research - Kaur, Navjeet; Arora, Pallvi (The journal of contemporary issues in business and government, 2021)
Values, beliefs, traditions, attitudes and behavioural patterns of a group of people together form the culture of that group that differentiates it from other groups. The objective of the research paper is to express the significance of cultural heterogeneity that exists within a nation for investigating national culture in an adequate and more explanatory manner rather than only focusing upon cultural homogeneity. This paper is based on the review of previously available secondary data in the domain of cultural studies. This paper argues that research studies focusing upon the intra-national cultural variations are important to recognize the culture of a country as a whole, and play a dominant role. The presence of heterogeneity in the Indian cultural system shall facilitate in deliberating upon the phenomenon of sub-cultural heterogeneity within a nation appropriately and efficiently enabling future research in the domain for more consistent outcomes. Majority of the cross- cultural management research studies conducted in the domain exclusively emphasized upon the cross-country cultural variations considering the entire nation as a single entity that lead to incorrect outcomes. It has been identified that there is a great need to acknowledge the importance of cross-cultural management research focusing upon intra-national cultural heterogeneity prevailing in a nation to achieve more accurate results.